Lysosomal and non-lysosomal peptidyl hydrolases of the bloodstream forms of Trypanosoma brucei brucei - Lonsdale-Eccles, John D.; Grab, D.J. (Wiley, 1987)
African trypanosomes have thiol‐dependent proteolytic activity that resembles some of the cathepsin‐like activity found in mammalian lysosomes [Lonsdale‐Eccles, J. D. & Mpimbaza, G. W. N. (1986) Eur. J. Biochem. 155, 469–473]. Here we show that this activity is found in lysosome‐like organelles which we have isolated (density = 1.082 g/cm3 in Percoll) from bloodstream forms of Trypanosoma brucei brucei. They are approximately 250 nm in diameter, are bounded by a single limiting membrane, and contain acid phosphatase. The predominant proteolytic and peptidolytic activity of these organelles has a pH optimum about 6.0, exhibits latency, and has the characteristics of mammalian cathepsin L (and possibly cathepsin H) with respect to its hydrolysis of small fluorogenic peptidyl substrates such as benzyloxycarbonyl‐phenylalanyl‐arginyl‐7‐amido‐4‐methylcoumarin. This substrate appears to be a good marker for trypanosomal lysosomes. The cathepsin‐L‐like activity is inhibited by the thiol‐protease inhibitors, E‐64, cystatin, leupeptin and mercurial compounds.The proteolytic activity of the lysosome‐like fraction is observed as a single band of activity with an approximate molecular mass of 27 kDa when measured after electrophoresis in the fibrinogen‐containing sodium dodecyl sulphate/polyacrylamide gels. The addition of mammalian serum to this purified fraction, or to whole trypansosome homogenates, results in the appearance of additional bands of activity, with a concomitant increase in the total observed proteolytic activity. The serum of some species of animal (e.g. goat and guinea pig) appear to lack the ability to generate this new and increased activity, while rat, rabbit, human and bovine sera exhibit varying capacities to generate the new activity, the cow being the most effective. The apparent molecular masses of the new bands of activity are different for each mammalian species, suggesting that the activator is a species‐specific molecule or class of molecules.We also show that Trypansosoma brucei contains soluble peptidolytic activity with an alkaline pH optimum. It is inhibited by the serine‐protease inhibitor diisopropylfluorophosphate, but not by inhibitors such as phenylmethylsulphonyl fluoride, α1‐antitrypsin, or aprotinin. Nor is it inhibited by the thiol‐protease‐specific inhibitors E‐64 or cystatin, although it is susceptible to inhibition by tosyllysylchloromethane, leupeptin, HgCl2 and p‐chloromercuribenzoate. This enzymic activity has a preference for arginyl residues in the primary binding site (the P1 position), as also does the activity from the lysosomes. However, the subsite specificity of the soluble enzymic activity is distinct from that of the lysosomes. The soluble enzyme(s) prefers small neutral molecules in the P2 and P3 subsites whereas the lysosomal enzyme(s) prefer hydrophobic molecules in these positions.